Apixaban Causing Hepatic Cystic Bleeding: A Rare but a Life-Threatening Complication - Elona Shehi (Karger Publishers, 2021)
Cystic lesions of the liver are a heterogeneous group of disorders with varied etiology, prevalence, and clinical manifestations. Fibropolycystic liver disease encompasses a spectrum of related liver and biliary tract lesions caused by abnormal embryologic development of the ductal plates. These disorders include congenital hepatic fibrosis, biliary hamartomas, polycystic liver disease (PCLD), choledochal cysts, and Carolis disease. PCLD is arbitrarily defined as a liver that contains >20 cysts. Most liver cysts are incidentally found on imaging studies, and the majority of the patients with liver cysts are asymptomatic. Rarely, complications such as compression, infection, and bleeding within the cyst can occur. Under the effect of the increased pressure, the epithelial lining of the cyst undergoes necrosis and sloughing, causing injury of the fragile blood vessels, leading to intracystic bleeding. The bleeding within or from the cyst can be precipitated by anticoagulation. We present a patient with PCLD who developed intracystic bleeding after he was started on apixaban for the prevention of thromboembolism.